2014
DOI: 10.1136/bcr-2014-204989
|View full text |Cite
|
Sign up to set email alerts
|

An unusual tale of rat-bite fever endocarditis

Abstract: SUMMARYA 49-year-old man presented to our department with an acute history of right leg tenderness, rash, swelling and fever. CT of the chest, abdomen and pelvis and a transoesophageal echocardiogram confirmed the diagnosis of mitral valve infective endocarditis with distal splenic emboli. Positive blood cultures revealed the causative organism to be Streptobacillus moniliformis. The patient was treated with high-dose antibiotics and had mitral valve replacement surgery. BACKGROUND

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
10
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“… 7 , 8 Consistent with our patient, approximately 30% of the patients recall no bite or other exposure. 4 , 6 Studies suggest that S. moniliformis may have a predilection for synovial and serosal surfaces. 4 , 9 …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“… 7 , 8 Consistent with our patient, approximately 30% of the patients recall no bite or other exposure. 4 , 6 Studies suggest that S. moniliformis may have a predilection for synovial and serosal surfaces. 4 , 9 …”
Section: Discussionmentioning
confidence: 99%
“…There have been three reviews of all of the previously reported cases of S. moniliformis endocarditis from 1915 to 2014. 6-7 , 10 Since these reviews, two more cases of RBF infectious endocarditis have been reported. 13 , 14 The diagnosis of endocarditis was most often established based on the clinical presentation, that included fever, rashes, and joint pains, a cardiac murmur, often without demonstrating a vegetation on echocardiogram, and a positive blood culture for S. moniliformis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…S. moniliformis is the causative agent of streptobacillary rat-bite fever 3 . It is also associated with amnionitis 4 , bacteremia 5 6 7 , brain abscess 8 , cutaneous and subcutaneous abscesses 9 10 , endocarditis 11 12 , female genital tract abscess 13 , palmoplantar pustulosis 14 , septic arthritis 15 16 17 , spinal epidural abscess 18 , splenic abscess 19 , spondylodiscitis with psoas abscess 20 , and synovitis 21 . Microbiologically, S. moniliformis is a Gram-negative facultative anaerobic bacillus that grows in chains.…”
mentioning
confidence: 99%